Distribusi dan Sex Ratio Udang Macrobrachium pilimanus pada Sungai Mengaji di Banyumas - Prodhiana Prodhiana; Moh. Husein Sastranegara; Elly Tuti Winarni (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The one forms of freshwater ecosystems which is the habitat of various organisms is rivers. The Mengaji River is a river that springs from the southern slopes of Mount Slamet. Rivers always experience changes in physical, chemical, and biological factors. The decline in river water quality greatly affects the distribution and sex ratio of Macrobrachium pilimanus in the Mengaji River. This research aims to determine the distribution and sex ratio of M. pilimanus shrimp in the Mengaji River. The research was conducted using a survey method for determining stations and purposive random sampling for sampling. The samples obtained were then identified and measured using the morphometric method. Research was conducted between June-August 2020. Shrimp distribution data were analyzed using the